Application of Data Mining to Predict Best-Selling Stationery Sales at Blessing Stationery Store Using the K-Nearest Neighbor (K-NN) Method - Maida Indrayani (BIOS: Jurnal Informatika dan Sains, 2024)
Stationery stands for office stationery that is used by various groups. Examples of stationery such as pencils, pens, erasers and so on. Toko Berkah ATK is one of the stores that sells office supplies. Sales of stationery at Toko Berkah ATK often decrease and increase every month. Depending on the needs of the people who buy at the ATK Blessing Store. To avoid the accumulation of ATK items that are not sold out, the application of data mining using the K-Nearest Neighbor (K-NN) method is carried out to predict the best-selling ATK sales at Toko Berkah ATK.